Work, Hustle, And Burnout: Narratives Of The Millennial And Gen-Z Workforce In Indonesian Fiction - Nurmayanti Nurmayanti (Journal of Literary Prose and Society, 2025)
This study examines representations of work culture, hustle ideology, and burnout in contemporary Indonesian fiction featuring millennial and Gen-Z protagonists. Employing qualitative literary analysis, the research analyzes 26 texts published between 2015-2024 through close reading and thematic coding frameworks. Findings reveal that 85% of texts explicitly engage with hustle culture, with 60% adopting critical narrative positions that expose contradictions between entrepreneurial promises and lived precarity. Burnout appears consistently across 92% of the corpus, depicted through sophisticated narrative techniques including fragmented syntax, non-linear chronology, and body metaphors that formally enact psychological suffering. The analysis demonstrates burnout as structural condition produced by toxic organizational systems, with 83% of fictional workplaces violating work-life boundaries and 67% exhibiting low psychological safety. Gendered patterns emerge significantly, with 80% of female protagonists experiencing burnout compounded by emotional labor expectations while 73% of male protagonists face provider pressures. Generational analysis reveals millennials express disillusionment from broken meritocratic promises while Gen-Z demonstrates baseline cynicism, though comparable burnout rates indicate structural conditions overwhelm individual attitudes. Individual resistance strategies appear in 54% of texts while collective organizing remains rare at 12%, suggesting literary reinforcement of neoliberal individualization. The research affirms literature's epistemic value for accessing subjective dimensions of work-related suffering while documenting cultural contestation around labor ideologies, contributing theoretical frameworks for analyzing Southeast Asian workplace fiction and practical evidence supporting policy interventions for labor protection, organizational transformation, and mental health support infrastructure.